Dynamic changes and prediction of land-use patterns in a typical area for rocky desertification control - Sang, Xu; Sun, Caili; Chai, Zongzheng (Frontiers in Ecology and Evolution, 2025)
IntroductionRocky desertification poses a significant ecological challenge globally, leading to ecosystem degradation and diminished land resources. Consequently, it causes substantial changes in land-use patterns, hindering regional sustainable development.MethodsThis research focuses on Bijie City, Guizhou Province, China, a region severely affected by rocky desertification. Using land use/cover data and relevant driving-factor data from 1990 to 2022, and employing methods such as spatial pattern analysis, we comprehensively analyze land-use/cover change (LUCC) characteristics over time and predict land-use patterns under three scenarios for 2030.ResultsThe key findings are: (1) Bijie City has diverse land types. Cropland and forest together comprise nearly 90% of the total land area, exhibiting distinct regional spatial distributions. (2) During the rocky desertification control period (1990–2020), cropland, shrubland, and grassland areas decreased, while forest area increased. Conversion of these three land types to forest was the primary driver of LUCC. Landscape fragmentation decreased, and the ecological environment significantly improved. (3) Projections indicate that focusing solely on ecological governance (Scenario 1) or cultivated-land protection (Scenario 2) is insufficient. Scenario 3, integrating ecological governance and cultivated-land protection, is optimal. By 2030, cropland area is projected to increase rationally by 307.51 km2, with some forest, shrubland, and grassland converting to cropland. This land-use change will be the main feature of future LUCC, safeguarding food security and enhancing ecological quality.DiscussionIn conclusion, rocky desertification control efforts from 1990 to 2020 have profoundly impacted Bijie City’s land-use patterns. Future efforts must prioritize coordinated ecological and cultivated land protection. This study provides crucial theoretical support for regional ecosystem management and spatial planning, promoting harmonious ecological and economic development.